ECF Key messages from the International Transport Forum 2011. - (:unkn) unknown (My University, 2011)
This paper includes the ECF´s main positions on the ITF 2011 key messages, a summary of the Ministers recommendation on national policies of promoting cycling and the Charter of Sevilla.
Keywords: Individualverkehr; Fahrrad; Verkehrspolitik; Fahrradförderung; Charta